CORPUS LINGUISTICS: A HISTORICAL OVERVIEW - Sukhrob Avezov Sobirovich (Bright Mind Publishing, 2025)
Corpus linguistics is a field of study that investigates language through large collections of texts (corpora). This article provides a historical overview of corpus linguistics, tracing its development from early textual analyses in pre-digital eras to the emergence of computerized corpora in the mid-20th century and the subsequent growth of the field. Key milestones such as the first computerized corpora in the 1960s, the expansion of corpus resources in the 1980s-1990s (the Brown Corpus, British National Corpus), and the integration of corpus-based methods into linguistics and language technology are discussed.
Keywords: Corpus linguistics, history of corpus linguistics, Brown Corpus, British National Corpus, text corpora, computational linguistics, lexicography, language analysis.